MENINGKATKAN KOMPETENSI PELAKU UMKM DALAM BERBISNIS MELALUI PELATIHAN HARGA POKOK PRODUKSI - Marieta Ariani; Hasnawati Zainal (Jurnal Abdimas Sangkabira, 2021)
The success of the company in determining the Selling Price of its business products is largely determined by the success of the company in determining or calculating the Cost of Production (HPP) of the products it produces.Errors in the determination of the cost of production (HPP) can cause errors in the determination of the selling price of the resulting product, so that the company cannot compete with other similar businesses.The difficulty of determining the cost of production and selling prices of fashion and culinary products experienced by MSME entrepreneurs has become a big problem and has been going on for a long time among kompeten member entrepreneurs in Bekasi, so continuous training is needed.This can also be used as a background or basis for scientific research by PKM lecturers, so that research results can be obtained that can answer the difficulties of entrepreneurs of KOMPETeN members of the Bekasi region in determining the cost of production and selling prices of fashion and culinary products.